2020
DOI: 10.1136/bmjopen-2019-034348
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the general practitioner’s sense of alarm when confronted with dyspnoea and/or chest pain: a prospective observational study

Abstract: ObjectivesDyspnoea and chest pain are symptoms shared with multiple pathologies ranging from the benign to life-threatening diseases. A Gut Feelings Questionnaire (GFQ) has been validated to measure the general practitioner’s (GPs) sense of alarm or sense of reassurance. The aim of the study was to estimate the diagnostic test accuracy of GPs’ sense of alarm when confronted with dyspnoea and chest pain.Design and settingsProspective observational study in general practice.ParticipantsPatients aged between 18 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…There have been many studies, showing the positive predictive value of gut feelings that lead to working hypotheses such as cancer, lung embolism and serious childhood infections. [26][27][28] Child abuse is often hidden, and a gut feeling might be an important signal to become suspicious, to observe more closely and to examine the child better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies, showing the positive predictive value of gut feelings that lead to working hypotheses such as cancer, lung embolism and serious childhood infections. [26][27][28] Child abuse is often hidden, and a gut feeling might be an important signal to become suspicious, to observe more closely and to examine the child better.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, we are in principle of the opinion that gut feelings are not right or wrong, but might raise the suspicion of a potentially serious problem, in our case that of child abuse, and might induce further diagnostics and actions. There have been many studies, showing the positive predictive value of gut feelings that lead to working hypotheses such as cancer, lung embolism and serious childhood infections 26‐28 . Child abuse is often hidden, and a gut feeling might be an important signal to become suspicious, to observe more closely and to examine the child better.…”
Section: Discussionmentioning
confidence: 99%
“…The INTERCHEST score includes the GP’s sense of alarm by administering points when the GP initially suspected a serious condition. A recent study by Barais et al 19 evaluated GPs sense of alarm using a validated ‘Gut Feelings Questionnaire’ in primary care patients presenting with chest pain and dyspnoea. The study showed that the probability of a life-threatening disease increases from 20% to 35% when a sense of alarm is present.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies regarding the use of gut feelings by GPs, hospital specialists, and nurses 9,[11][12][13][14][15][16][17] . GPs reported using their gut feelings in suspecting cancer 9,[17][18][19][20] and other serious diseases 21,22 .…”
Section: Introductionmentioning
confidence: 99%